Post-Pandemic: University Students' Satisfaction on The Use of E-Learning - Kee, Daisy Mui Hung; Liew, John Hong En; Heng, Jeanlu; Ng, Joshua Chun Kith; Jani, Kelly; Antika, Dini Kurnia; Purwatiningsih, Eli (AIBPM Publisher, 2023)
In 2020, approximately all universities worldwide abruptly closed due to an urgent public health issue to stop the COVID-19 epidemic from spreading. Unfortunately, even though some universities have undergone online teaching techniques before, they are not prepared to learn online fully. This research examines whether students' attitudes, convenience flexibility, and schools' support influence the continuance intention toward e-learning and whether satisfaction with e-learning is the mediator of the relationships above. This study was conducted in Malaysia and Indonesia after the COVID-19 epidemic to assess university students' intent to continue using e-learning platforms. 160 college students in all took part in the research. This study reveals that satisfaction directly influences continuance intention whereas convenience flexibility and school support influence continuance intention when satisfaction came in and plays a role as a mediator. The link between students’ attitudes, convenience flexibility, school support, and continuance intention is mediated by their satisfaction with e-learning.